Age-adjusted mortality rates of neoplasms and circulatory system diseases and their demographic factors in Slovak regions during 1996-2013 - Pella, Daniel; Fedačko, Ján; Rajnoha, Rastislav; Gavurová, Beáta; Koróny, Samuel (Central European Journal of Public Health, 2017)
AIM: Knowledge of the causes of deaths in Slovakia is lacking. This is significant because diet and lifestyle factors are different in central Europe compared to Western, Northern and Southern Europe. This study aims to discern trends of age-adjusted mortality rates caused by various diseases in relation to demographic factors. The aim of our study was to find certain statistical aspects including trends of age-adjusted mortality rates caused by neoplastic (Chapter II) and circulatory diseases (Chapter IX) in the Slovak population in relation to available demographic factors (sex, region and calendar year of death). METHODS: Dataset of individual deaths in Slovakia with certain demographic factors (sex, region and calendar year of death) during 1996-2013 were provided by the Slovak National Center of Health Informatics. Regression and correlation analyses and analyses of variance and of covariance were used to yield the level of significance. RESULTS: We found significant differences of age-adjusted mortality rates between men and women, between Chapter II and Chapter IX and among Slovak regions. Age-adjusted mortality rates decline significantly in most regions for both sexes with the exception of stagnation in four regions in a group of Chapter II women (Košice, Nitra, Trenčín and Žilina) and one region in Chapter IX, also in group of women (Žilina). CONCLUSIONS: Mortalities caused either by Chapter II or Chapter IX diseases are significantly dependent on chapter, sex and region with mortalities either declining or stagnating.
Keywords: Demography; kardiovaskulární nemoci; Humans; lidé středního věku; Female; rizikové faktory; Aged; věkové faktory; senioři; lidé; Slovakia; Slovenská republika; ženské pohlaví; Cardiovascular Diseases; Male; Middle Aged; Neoplasms; Aged, 80 and over; nádory; demografie; senioři nad 80 let; Age Factors; mužské pohlaví; Risk Factors